2021
DOI: 10.1097/der.0000000000000726
|View full text |Cite
|
Sign up to set email alerts
|

Patch Testing During Immunosuppressive Therapy: A Systematic Review

Abstract: Patch testing, used in the assessment of allergic contact dermatitis, is ideally avoided in patients receiving immunosuppressive therapy because of concerns with reductions in accuracy; however, this is not well characterized in the literature. This systematic review summarizes patch testing results in patients receiving immunosuppressive therapy. We identified 16 studies, comprising 195 patients with dermatitis or psoriasis, who were patch tested while receiving immunosuppressants. Of these, 7 studies, compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…This type of psoriasis appears to be immunologically distinct from classical psoriasis, and some cases were described as ‘‘psoriasiform’’ because they did not necessarily meet the definition of psoriasis [ 66 , 67 , 68 , 69 , 70 ]. Although a switch in the polarization of the predominant immune response from Th 2 to Th 17 was hypothesized, a deeper understanding of the mechanism behind this reaction to dupilumab will lead to the complete comprehension of the immunopathogeneses of psoriasis and atopic dermatitis [ 71 ]. A recent systematic review by Mufti et al assessing studies with dermatitis patients patch-tested before and during various treatments reported that almost 68% of the patients who received dupilumab maintained positive patch testing results to an allergen that was previously graded as a significant positive reaction [ 72 ].…”
Section: Psoriasis Biologics and Skin Patch Testingmentioning
confidence: 99%
“…This type of psoriasis appears to be immunologically distinct from classical psoriasis, and some cases were described as ‘‘psoriasiform’’ because they did not necessarily meet the definition of psoriasis [ 66 , 67 , 68 , 69 , 70 ]. Although a switch in the polarization of the predominant immune response from Th 2 to Th 17 was hypothesized, a deeper understanding of the mechanism behind this reaction to dupilumab will lead to the complete comprehension of the immunopathogeneses of psoriasis and atopic dermatitis [ 71 ]. A recent systematic review by Mufti et al assessing studies with dermatitis patients patch-tested before and during various treatments reported that almost 68% of the patients who received dupilumab maintained positive patch testing results to an allergen that was previously graded as a significant positive reaction [ 72 ].…”
Section: Psoriasis Biologics and Skin Patch Testingmentioning
confidence: 99%
“…There are no data about the efficacy or safety of patch testing under ICPI conditions. Just as immunosuppression risks false‐negative results, 7 an immune‐enhanced anti‐PD‐1 state could theoretically cause allergy induction, severe patch test reactions and false positives. We considered titrated PPD patch testing at 0.01% 8 .…”
Section: Discussionmentioning
confidence: 99%
“…All Although there was variability in reported minimum withdrawal times from topical anti-inflammatory use at test site, UV exposure, and intramuscular or oral corticosteroid use, the consensus was consistent with previously published practices (Table 1). 4 A majority (>50%) reported that they would patch test during traditional dosing of tumor necrosis factor α inhibitors, apremilast, antihistamines, and omalizumab without reservation (Fig. 1; Supplementary Figure 1, http://links.lww.com/ DER/A96).…”
Section: Expert Opinion On Patch Testing While Receiving Immunomodula...mentioning
confidence: 99%